Kondi?loma akümi?nata ve tedavi? yöntemleri? - Aygün, Banu Kumbak; Çelik, Hüsnü; Kavak, Burçin; Gürateş, Bilgin (My University, 2009)
Condylomata acuminata, genital warts, are a common sexually transmitted disease in developed countries and its prevalance is increasing with time. Human papillomavirus (HPV) is the cause of genital warts and the viral activity depends on the immune status of the infected individual. Spontaneous regression of warts is seen in up to 20% of the cases. Various treatment modalities have been described which can be separated into topical cytotoxic (bi/trichloroacetic acid, podophyllin, podophyllotoxin, 5-fluorouracil, green tea catechins), immunomodulatory (imiquimod, interferon, Candida or mumps antigen, Bacillus Calmette-Guerin (BCG), oral inosiplex) and ablative/destructive surgery (cryotherapy, laser, electrocauterization, surgical excision). Multiple treatment approaches exist for the management of genital warts, therefore treatment method decisions are based upon the number, size, extent and location of warts, co-existing medical conditions (e.g. immunodeficiency, pregnancy), and patient and physician preferences as well. Among such a large spectrum of treatment alternatives, no one therapeutic modality is superior to others and various recurrence rates have been reported for all of the methods, ranging between 30-70%. As there is currently no cure for HPV infection and a causal role for HPV infections in cervical cancer has been documented, preventive measures are increasingly important. New vaccine therapy for prevention of infection promise to reduce the incidence of disease.
Keywords: Condylomata acuminata; Genital warts; Human papillomavirus (HPV); Treatment